Verification results of jet resonance-enhanced multiphoton ionization as a real-time PCDD/F emission monitor - Gullett, Brian; Oudejans, Lukas; Touati, Abderrahmane; Ryan, Shawn; Tabor, Dennis (Journal of material cycles and waste management, 2008)
A jet resonance-enhanced multiphoton ionization (REMPI) monitor was tested on a hazardous-waste-fired boiler for its ability to determine concentrations of polychlorinated dibenzodioxins and dibenzofurans (PCDDs/Fs). Jet REMPI is a real-time instrument capable of highly selective and sensitive (from parts per billion to parts per trillion) detection of a broad range of aromatic compounds, including a number of air toxic compounds. The PCDD/F toxic equivalency (TEQ) value was derived from a predetermined correlation ( R 2 = 0.74) with monochlorobenzene (MClBz). This relationship was applied to nine subsequent jet REMPI on-line measurements of MClBz and parallel, standard extractive sampling for PCDD/F TEQ. For high waste-firing rates, with a range of PCDD/F TEQ values between 3.9 and 6.0 ng TEQ/m 3 , the TEQ values predicted by jet REMPI had a relative difference of 26% with the standard EPA Method 23 results. At low waste-firing rates (0.9–1.6 ng TEQ/m 3 ), the relative difference increased to 219%. This limited testing shows that jet REMPI has promise as an on-line diagnostic monitor, providing feedback on the effects on PCDD/F emissions of operating parameter changes such as fuel feed interruptions or air pollution control failures.